1996
DOI: 10.1177/01461672962211008
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup Anxiety: A Person × Situation Approach

Abstract: A person × situation approach to the study of intergroup anxiety is offered in which anxiety in intergroup encounters is viewed as a transaction between the individual and the environment. An individual difference measure of intergroup anxiety toward African Americans is developed, and studies assessing the scale's reliability and validity are presented. The utility of a person × situation approach is shown in an experiment in which participants high or low in intergroup anxiety were told they would interact w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
119
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 35 publications
11
119
0
2
Order By: Relevance
“…To test our hypothesis, we collected separate measures of evaluative and semantic racial associations in White participants as they prepared to interact with either a Black or White discussion partner (Britt, Boniecki, Vescio, Biernat, & Brown, 1996). This context provided a method for eliciting intergroup anxiety in a realistic yet experimentally controlled situation.…”
Section: Study Overviewmentioning
confidence: 99%
“…To test our hypothesis, we collected separate measures of evaluative and semantic racial associations in White participants as they prepared to interact with either a Black or White discussion partner (Britt, Boniecki, Vescio, Biernat, & Brown, 1996). This context provided a method for eliciting intergroup anxiety in a realistic yet experimentally controlled situation.…”
Section: Study Overviewmentioning
confidence: 99%
“…Stereotypes have been suggested to lead to intergroup anxiety, which in turn results in avoidance, con®rmatory biases, negative emotional responses, and negative evaluations of minorities (e.g. Britt, Boniecki, Vescio, Biernat & Brown, 1996;Stephan & Stephan, 1985, 1989a,b, 1992Stephan, Stephan, Wenzel & Cornelius, 1991). It has also been suggested that arousal and some forms of emotional experience (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, empirical research relying on the Spielberger's STAI (State-Trait Anxiety Inventory), for instance, has demonstrated that "the common latent trait variable of repeatedly measured anxiety states was strongly correlated with the common latent trait variable of the repeatedly administered trait scale" [34], which supports the assumption that, although states can be measured, there is always a latent trait with the necessary power to explain behaveioural variance. In fact, the idea that traits influence psychological states is an established one [36].…”
Section: Immutability Of Traitsmentioning
confidence: 99%